A Catalytic and Interfacing PEDOT:PSS/CuPc Polymerized on Cloth Fiber to Electro‐Metalize Stretchable Copper Conductive Pattern. Issue 16 (5th December 2021) - Li, Jing; Zhou, Guoyun; Hong, Yan; Chen, Chia‐Yun; He, Wei; Wang, Shouxu; Chen, Yuanming; Wang, Chong; Sun, Yukai; Wong, Chingping
Abstract: Copper conductive pattern should provide dependent flexibility on coated cloth‐fiber to support the signal transmission or current carrier for stretchable and reliable electronics. The design of copper phthalocyanine (CuPc) introduced in poly(3, 4‐ethylenedioxythiophene) and polystyrene sulfonate acid (PEDOT:PSS) polymer network promotes the realization of copper electro‐metallization from its inner active dots, leading to a structure of PEDOT:PSS/CuPc‐rooted copper coating. The bridge‐layer of elastic PEDOT:PSS/CuPc interfacing and catalyzing the copper layer with excellent ductility and antioxidation, is developed to sustain the required stretchability for electronics on regular cloth polyurethane fiber. Experimental results demonstrate that this design achieves a perfect 80% conductivity of bulk copper, an ignored resistance changes after bending test, tensile test, 10 days' natural oxidation, and 10 times' machine‐washing, respectively. Accordingly, a breakthrough is made to supply the compatible integrity of copper line on cloth fiber for wearable electronics. Abstract : The design of CuPc introduced in poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) promotes the realization of copper electro‐metallization from its inner active dots, leading to a structure of PEDOT:PSS/CuPc‐rooted copper coating. The deposited copper pattern is capable of enduring repetitive bending, stretching, and even machine washing, which shows that the fabricated circuit meets the requirements of electrical and mechanical stability of wearable clothing.